Offshore wind power policies and green total factor productivity: empirical evidence from coastal China - Zhang, Junjie; Wei, Zhuxia (Frontiers in Ecology and Evolution, 2023)
Green and high-quality development requires the transformation and upgrading the energy structure.As a clean and efficient new energy,the development of offshore wind power is related to the achievement of green development and the realization of the dual carbon goals. Based on the perspective of green total factor production, this study aims to explore the impact of offshore wind power policies(OWPPs) on green and high-quality development. Taking 11 coastal areas of China from 2004 to 2020 as samples, this paper empirically tested the impact of OWPPs on green total factor productivity(GTFP) by using propensity score matching difference-in-differences method (PSM-DID). The results show that OWPPs have a significant positive impact on GTFP. The robustness test further verifies the results, and the provincial difference is significant. By stimulating technological innovation and reducing energy intensity, OWPPs have improved GTFP, but increasing marketization level is a long way off.China for the first time. SBM-GML model and more comprehensive indicators are used to measure GTFP. OWPPs have significantly promote the GTFP in the pilot regions, specifically by influencing the technology change component of the GTFP. Heterogeneity exists between the GTFP of OWPPs and the regions. Technological innovation and energy intensity are mechanisms, marketization level faces numerous challenges.